Laser-based directed energy deposition of Monel K-500 and Stellite 6 multi-materials - Chen, Ze (2024)
Laser-based directed energy deposition (L-DED) offers significant advantages for repairing metal structures, particularly in the marine and offshore industry where corrosion-resistant materials like Monel K-500 (a Ni-Cu alloy) lack strength and wear resistance. This study addresses this issue by producing Monel K-500 with high-strength Stellite 6 (a Co-Cr alloy). Two types of multi-material samples were created using L-DED: interlayered and mixed powder samples. The interlayered samples experienced cracking at the material interface, while the mixed powder samples were crack-free and exhibited improved mechanical properties, with yield strength increasing from 208.3 MPa to 490.2 MPa and ultimate tensile strength from 429.7 MPa to 887.0 MPa compared to single Monel K-500 samples. This research demonstrated the potential of in-situ alloying during the L-DED process to enhance alloy properties and highlighted the challenges of abrupt compositional changes leading to cracking, suggesting mitigation strategies for successful production.